آیاتِ الاحکام پر لکھی گئی عربی کتب کا تعارفی و تجزیاتی مطالعہ : An Introductory and Analytical Study of Arabic Works on Āyāt al-Aḥkām (Al-NASR, 2024)
This study offers a comprehensive introductory and analytical review of major Arabic works authored on Āyāt al-Aḥkām, examining their historical development, scholarly objectives, and distinctive methodological approaches. It critically analyzes how classical and modern exegetes interpret Qur’anic legal verses through linguistic analysis, principles of uṣūl al-fiqh, ḥadīth evidence, and comparative juristic reasoning, while also highlighting the influence of different schools of Islamic law. The research underscores the academic significance of these works in the formation, interpretation, and application of Islamic legal rulings and their continued relevance in contemporary legal and scholarly discourse.
Keywords: Āyāt al-Aḥkām; Qur’anic Legal Verses; Islamic Jurisprudence; Fiqh Methodology; Classical Arabic Tafsīr; Qur’anic Studies; Hadith Studies; Comparative Religion